Podoplanin: Its roles and functions in neurological diseases and brain cancers - Wang, Yi; Peng, Dan; Huang, Yaqian; Cao, Yongjun; Li, Hui; Zhang, Xia (Frontiers in Pharmacology, 2022)
Podoplanin is a small mucin-like glycoprotein involved in several physiological and pathological processes in the brain including development, angiogenesis, tumors, ischemic stroke and other neurological disorders. Podoplanin expression is upregulated in different cell types including choroid plexus epithelial cells, glial cells, as well as periphery infiltrated immune cells during brain development and neurological disorders. As a transmembrane protein, podoplanin interacts with other molecules in the same or neighboring cells. In the past, a lot of studies reported a pleiotropic role of podoplanin in the modulation of thrombosis, inflammation, lymphangiogenesis, angiogenesis, immune surveillance, epithelial mesenchymal transition, as well as extracellular matrix remodeling in periphery, which have been well summarized and discussed. Recently, mounting evidence demonstrates the distribution and function of this molecule in brain development and neurological disorders. In this review, we summarize the research progresses in understanding the roles and mechanisms of podoplanin in the development and disorders of the nervous system. The challenges of podoplanin-targeted approaches for disease prognosis and preventions are also discussed.